2012
DOI: 10.2147/ijn.s36257
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization and in vivo evaluation of nanostructured lipid curcumin carriers for intragastric administration

Abstract: Background:Curcumin has a variety of pharmacological effects. However, poor water solubility and low oral bioavailability limit its clinical utility. A delivery system for nanostructured lipid carriers has been reported to be a promising approach to enhancing the oral absorption of curcumin. The aim of the present study was to investigate the pharmacokinetics, tissue distribution, and relative bioavailability of curcumin in rats after a single intragastric dose of a nanostructured lipid curcumin carrier formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 29 publications
4
31
0
Order By: Relevance
“…Interestingly, the results also construed that the effect of increase in the levels of liquid lipid was responsible for evaluating drug release rate, ostensibly owing to loosening of the packing of drug within the lipid matrix (Dhawan et al, 2010). Mgf's PLCs-loaded NLCs exhibited sustained drug release profile, considered to be essential for enhancing the therapeutic response for prolonged period of time (Fang et al, 2012;Tran et al, 2014).…”
Section: Encapsulation Efficiencymentioning
confidence: 98%
“…Interestingly, the results also construed that the effect of increase in the levels of liquid lipid was responsible for evaluating drug release rate, ostensibly owing to loosening of the packing of drug within the lipid matrix (Dhawan et al, 2010). Mgf's PLCs-loaded NLCs exhibited sustained drug release profile, considered to be essential for enhancing the therapeutic response for prolonged period of time (Fang et al, 2012;Tran et al, 2014).…”
Section: Encapsulation Efficiencymentioning
confidence: 98%
“…Adjuvants, nanoparticles, micelles, phospholipid delivery systems, and liposomes have been tested to overcome this problem (2,16,18,19). There are several curcumin formulations that can improve the bioavailability of curcumin in human.…”
mentioning
confidence: 99%
“…Nanoparticles can promote particle recognition of the ReS by organs such as liver, lung and spleen by opsonization processes (20,21). This study revealed that uptake of nanoparticles from capillaries of the parietal peritoneum into the target organ might lead to Cur-NLC distributed to lung tissue more intensively than native curcumin.…”
Section: Tissue Distribution Studymentioning
confidence: 85%